2017
DOI: 10.22260/isarc2017/0106
|View full text |Cite
|
Sign up to set email alerts
|

Leading Safety Indicators and Automated Tools in the Construction Industry

Abstract: Hong Kong is one of the cities with the largest number of skyscrapers. In this paper, we study the factors that lead to construction accidents on sites by interviewing the relevant parties. In the second part of the research, we extract the causes of accidents from court case report. Last but not least, we include a single case study from one of the largest construction companies in Hong Kong where robotics, drones, three-dimensional printing, virtual reality, wearable robotics and so on are applied on constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Augmented reality enhances reality by using technology to do so (Patrucco et al 2010). Health and safety managers use both technologies to review safety tie-off points and create a genuine health and safety work experience through virtual drills, instructions, and health and safety scenarios viable for construction health and safety training (Li and Leung 2017;Zhang et al 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Augmented reality enhances reality by using technology to do so (Patrucco et al 2010). Health and safety managers use both technologies to review safety tie-off points and create a genuine health and safety work experience through virtual drills, instructions, and health and safety scenarios viable for construction health and safety training (Li and Leung 2017;Zhang et al 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Teizer et al (2007) revealed that through the application of emerging technologies in health and safety, construction workers could be provided with layers of protection. Previous research efforts have explored the interaction and collision between heavy equipment and workers on construction sites (Li and Leung, 2017). The awareness of workers and visibility of equipment operators decreases because of the repetitive nature of construction activities (Teizer et al, 2007).…”
Section: People Technologiesmentioning
confidence: 99%
“…Numerous studies have identified automation and robotics as effective technologies with good prospects to enhance proactive workers' safety on construction sites (Zhou et al, 2011). Automated platforms have been developed for the construction of high-rise structures (Li and Leung, 2017). This building system requires less labour and aims to reduce and eliminate injuries caused by over-exertion (Teizer, 2015).…”
Section: People Technologiesmentioning
confidence: 99%
See 2 more Smart Citations